How Does the Displacement of Natural Persons during War Influence the Applicable Law - Dikovska, Iryna; Wałachowska, Monika (Problemy Prawa Prywatnego Międzynarodowego, 2022)
In this article the authors analyse the consequences of displacement of natural persons during war, in the field of private international law. That displacement may affect the determination of applicable law if the factors to be taken into account include domicile, habitual residence, permanent residence, residence or sojourn of natural person. Apart from discussing the general understanding of these factors, we present the situations where a person has lost links with the country of his or her nationality because of the war but has not acquired strong links with any other country. All of the issues are discusses in the light of legal assistance agreements, EU law, and national laws.